Patenting Foundational Technologies: Lessons From CRISPR and Other Core Biotechnologies. Issue 12 (2nd December 2018) - Feeney, Oliver; Cockbain, Julian; Morrison, Michael; Diependaele, Lisa; Van Assche, Kristof; Sterckx, Sigrid
Abstract : In 2012, a new and promising gene manipulation technique, CRISPR-Cas9, was announced that seems likely to be a foundational technique in health care and agriculture. However, patents have been granted. As with other technological developments, there are concerns of social justice regarding inequalities in access. Given the technologies' "foundational" nature and societal impact, it is vital for such concerns to be translated into workable recommendations for policymakers and legislators. Colin Farrelly has proposed a moral justification for the use of patents to speed up the arrival of technology by encouraging innovation and investment. While sympathetic to his argument, this article highlights a number of problems. By examining the role of patents in CRISPR and in two previous foundational technologies, we make some recommendations for realistic and workable guidelines for patenting and licensing.